PENGELOMPOKAN BERBAGAI MERK MI INSTAN BERDASARKAN KEMIRIPAN KANDUNGAN GIZI DENGAN MENGGUNAKAN ANALISIS BIPLOT - ETE, AGUSTINUS ANGELAUS; SUCIPTAWATI, NI LUH PUTU; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 3 No 2 (2014)DO - 10.24843/MTK.2014.v03.i02.p066, 2014)
At this time, almost everyone once to consume instant noodles. The high interest of public on the instant noodles should be balanced with enough knowledge about the noodles and its nutritional content, either on it’s instant noodles which have similar nutrient content and nutrient content that become identifier of each this group of noodles. The method can be used to obtain information on several brands of instant noodles that have similar nutrient content and nutrient content type that become identifier of each group of instant noodles is biplot analysis. Biplot analysis can show mie and nutrient content types simultaneously in a two-dimension plot. So that from a plot shows noodles and nutritional content types simultaneously, so that obtain information about the instant noodle that have similar nutrient content and nutrient content types into identifier of each group of instant noodles. This study was used 33 brands of instant noodles as observed objects with the type of nutrient content were observed there were nine. This study aims to find out some instant noodles that have similar nutrient content and nutrient content type that become identifier of each group of instant noodles. From the biplot analysis, obtained six groups of instant noodles with different identifier variables.
Keywords: Biplot Analysis, Similarity, Type of Nutrition